Optimization of large-scale wind-powered centrifugal pumps. Issue 5 (October 2019) - Siddig, Mohammed Hashim
A study on the optimal matching of centrifugal pumps and large-scale wind turbines is reported. The study includes mathematical modelling of the performance of high-capacity centrifugal pumps when matched with efficient high-speed low-solidity wind turbines. The dependence of the performance of wind pumps on the dimensionless parameter v /√( gh ), termed the wind pump's Froude number, was fully analysed. Similar to earlier reported results on wind-powered piston pumps, analysis is showing that the wind pump's Froude number is the dominant independent dimensionless parameter that fully defines the system's performance. Operation with continuous variable transmission was analysed and shown to optimize the wind pump's performance, particularly at medium and low wind speeds. The optimum relation between the required gearbox transmission ratio and Froude number of a wind-powered centrifugal pump was analytically established for three different pumps. In addition to continuous variable transmission operation, the analysis helps in optimally sizing constant transmission ratio systems.